Hubungan Kualitas Tidur dengan Fatigue pada Pasien Penyakit Paru Obstruktif Kronik (PPOK) - Christine Handayani Siburian; Hamonangan Damanik; Ratna Dewi; Meriani Herlina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a preventable and treatable disease characterized by persistent respiratory symptoms and airflow limitation. The existence of sleep disorders experienced by sufferers certainly will not be able to restore and restore the body's condition properly and cannot rest his body properly. This situation results in irritability, fatigue, dizziness, anxiety, and stress which will affect the quality of life of these sufferers. This research design is quantitative which is used to examine certain populations or samples. The method used in this research is an analytic survey with a cross-sectional approach, namely a study to determine the relationship and level of relationship between two or more variables without any effort to influence these variables so that there is no variable manipulation. The number of samples is 30 people with accidental sampling technique. The research results obtained results p value = 0.004. This figure shows a very strong correlation between sleep quality and fatigue in COPD patients. It is suggested that the results of this study can be used as material for policy making in improving health services for patients with Chronic Obstructive Pulmonary Disease (COPD).